Biomass-based hard carbon material with closed-pore structure optimized by boron-based template agent, preparation method of biomass-based hard carbon material and application of biomass-based hard carbon material in sodium-ion battery
By optimizing the preparation method of biomass-based hard carbon materials through boron-based templates, the problem of insufficient regulation of the closed-pore structure of hard carbon materials was solved, and the electrochemical performance and cycle stability of sodium-ion batteries were improved.
Patent Information
- Application Number
- CN202510862878.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-25
- Publication Date
- 2025-09-26
AI Technical Summary
Existing hard carbon materials have insufficient regulation of closed-pore structure in sodium-ion batteries, resulting in low capacity in the low-pressure platform area, low first Coulombic efficiency and poor cycling performance. In addition, the component heterogeneity of biomass precursors and traditional carbonization processes lead to low efficiency in closed-pore formation.
A boron-based template is mixed with a biomass precursor, and the closed-pore pore size and volume of the hard carbon material are regulated through low-temperature pre-carbonization and high-temperature re-carbonization treatment. The boron-based template forms a physical protective layer during the carbonization process, which blocks the escape channel of light volatile products and optimizes the closed-pore structure.
It improves the rate performance, cycle performance and first coulombic efficiency of sodium-ion batteries, enhances the sodium ion storage sites, and improves the electrochemical performance of the battery.
Smart Images

Figure CN120698438A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a biomass-based hard carbon material with a closed-pore structure optimized by a boron-based template, a preparation method thereof, and an application thereof in sodium ion batteries. Background Art
[0002] In the negative electrode material system of sodium-ion batteries, hard carbon materials have become the preferred materials for the negative electrode of sodium-ion batteries due to their unique disordered turbulent layer structure (interlayer spacing>0.37nm), rich pore structure and good adaptability to a wide temperature range. Its pore structure can provide high sodium storage capacity. However, existing hard carbon materials generally face the problem that the coordinated regulation mechanism of multi-level pore structure (micropore / mesopore / closed pore) is not yet clear, and the insufficient closed pore volume leads to low capacity in the low-pressure platform area. This bottleneck directly restricts the improvement of the low-pressure platform sodium storage capacity and initial coulombic efficiency (ICE) of hard carbon, and these two key parameters are the core requirements for building high-energy-density sodium-ion batteries.
[0003] Among existing preparation technologies, biomass-derived hard carbon has the advantage of renewable raw materials, but its industrial application is limited by two core issues. (1) The component heterogeneity of the biomass precursor (fluctuation in the ratio of cellulose / lignin / hemicellulose) leads to uncontrollable pore evolution during the carbonization process; (2) The traditional carbonization process (direct high-temperature pyrolysis) forms open escape channels due to the release of tar, resulting in low closed-pore formation efficiency. In order to further improve the energy density and cycle stability of sodium-ion batteries, it is urgent to develop a new hard carbon material preparation method to obtain hard carbon materials with high closed-pore volume to meet the performance requirements of sodium-ion battery anode materials. Summary of the Invention
[0004] The present invention aims to overcome the problem of insufficient closed-pore structure regulation in biomass hard carbons in the prior art, which leads to low initial coulombic efficiency (ICE) and reduced rate and cycle performance of batteries. The present invention provides a biomass-based hard carbon material with an optimized closed-pore structure using a boron-based template and a method for preparing the material. The present invention precisely regulates the closed-pore pore size and volume of the hard carbon material, increasing the number of sodium ion filling sites and isolating the electrolyte from direct contact with the effective sodium storage sites within the closed pores, thereby improving the battery's rate performance, cycle performance, and initial coulombic efficiency.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The first aspect of the present invention provides a method for preparing a biomass-based hard carbon material with a closed-pore structure optimized by a boron-based template, comprising the following steps:
[0007] (1) solid-liquid mixing of biomass and a boron-based template aqueous solution, and drying;
[0008] (2) The mixed material is subjected to two carbonization treatments, firstly, low-temperature pre-carbonization is performed to convert the boron-based template into a boron-based template at low temperature and embed it into the biomass precursor carbon. After natural cooling, the boron-based template is washed to remove the boron-based template. Then, the mixed material is subjected to high-temperature re-carbonization, followed by crushing, acid washing, water washing and drying in sequence to obtain the hard carbon material.
[0009] Preferably, in step (1), the biomass is at least one of bamboo, pulp, lignin, walnut shells, tea oil shells, xylose residue, coconut shells, fruit cores, peanut shells, nut skins, corn cobs, straw and cellulose powder.
[0010] Preferably, in step (1), the boron-based template is at least one of boric acid, borax, triethyl borate, trimethyl borate, metaboric acid, sodium metaborate, and potassium borate.
[0011] Preferably, in step (1), the mass ratio of the boron-based template to the biomass is 0.01:1-0.5:1.
[0012] Preferably, in step (2), the boron-based template is removed by washing with dilute hydrochloric acid at a concentration of 0.1-3 mol / L, and deionized water is used to wash away the residual hydrochloric acid in the hard carbon.
[0013] Preferably, in step (2), the low-temperature pre-carbonization is carried out under the protection of an inert atmosphere, and the carbonization conditions include: a heating rate of 2-20°C / min, a temperature of 200-600°C, and a holding time of 10-300min.
[0014] Preferably, in step (2), the high-temperature recarbonization is carried out under the protection of an inert atmosphere, and the carbonization conditions include: a heating rate of 2-20°C / min, a temperature of 1200-1600°C, and a holding time of 10-300min.
[0015] Preferably, in step (2), the pickling is carried out using an acidic solution comprising at least one of hydrochloric acid, sulfuric acid, phosphoric acid and nitric acid, wherein the acid concentration is 0.1-3 mol / L.
[0016] The second aspect of the present invention provides a biomass-based hard carbon material with a closed-pore structure optimized by a boron-based template prepared by the above method.
[0017] The third aspect of the present invention provides the use of the above-mentioned biomass-based hard carbon material with a closed-pore structure optimized by a boron-based template as a negative electrode material for sodium ion batteries.
[0018] A fourth aspect of the present invention provides a sodium ion battery, the negative electrode of which contains the above-mentioned biomass-based hard carbon material with a closed-pore structure optimized by a boron-based template.
[0019] By the above technical scheme, the amorphous carbon near the biomass is activated and catalyzed by a boron-based template, the microporous structure of the hard carbon material is effectively regulated, and the degree of graphitization of the material is improved, and the dead sodium situation caused by SEI is finally alleviated, while more sodium storage sites are provided, thereby improving the cycle capacity and rate performance of the battery. The outermost layer of the boron atom has only 3 electrons, has strong electron deficiency, and is easy to form a coordination bond or covalent bond (such as BO bond) with the biomass precursor (electron-rich groups such as oxygen and nitrogen). This interaction can effectively regulate the local chemical reaction in the carbonization process, and is also conducive to the boron-based template being uniformly dispersed in the biomass, while other non-boron elements (such as K, Cl) lack this bonding ability, and only leave macroscopic pores by melting-washing, and it is impossible to regulate the optimization of carbon layer arrangement and closed-pore structure at the atomic scale. The comparative experimental results show that when a template (such as potassium chloride, comparative example 4) without boron element is used, the electrochemical performance of the obtained hard carbon material is significantly reduced, specifically manifested as the reversible capacity and first coulomb efficiency of hard carbon are greatly reduced. This result confirms the key role of boron-based templates. Non-boron-based templates have difficulty interacting effectively with biomass precursors, resulting in an inability to exert a uniform template effect, which in turn hinders the formation and optimization of the closed-pore structure within the hard carbon material.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] This method uses biomass and a boron-based template as raw materials. The boron-based template acts as a closed-cell structure regulator. During the heating and carbonization process, the boron oxide produced by the low-temperature decomposition of the boron-based template acts as a template embedded in the biochar precursor and also serves as a physical protective layer, hindering the release of light volatile products from biomass pyrolysis. Compared to other methods for producing hard carbon using biomass materials, this method is environmentally friendly, simple, practical, low-cost, and has the advantages of high performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 1 is a charge and discharge curve diagram of the hard carbon material obtained in Example 1 and Comparative Example 1.
[0023] Figure 2 2 are XRD patterns of the hard carbon materials obtained in Example 1 and Comparative Example 1.
[0024] Figure 3 The closed pore volume and capacity relationship diagram of the hard carbon materials prepared in Examples 1-10 and Comparative Examples 1-4 are drawn.
[0025] Figure 4 This is the TEM image of the hard carbon material prepared in Example 8. DETAILED DESCRIPTION
[0026] To make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely below. Where specific conditions are not specified in the embodiments, conventional conditions were used. Where the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0027] Example 1
[0028] This embodiment provides a method for preparing a hard carbon material with a closed-pore structure optimized by a boron-based template, and the specific steps are as follows:
[0029] Boric acid and an appropriate amount of deionized water were added to a reaction vessel to dissolve the boric acid. Cellulose powder was then added to a ratio of 5 wt.% boric acid to cellulose powder. The mixture was mechanically stirred until thoroughly mixed. The resulting mixture was transferred to a heater for drying at 80°C for 12 hours. The dried mixture was pre-carbonized at low temperature under a nitrogen atmosphere at a heating rate of 5°C / min to a carbonization temperature of 400°C for 2 hours. After natural cooling, the boron oxide template was removed by washing with 0.1 mol / L hydrochloric acid, and residual hydrochloric acid was removed by washing with deionized water. After drying, the pre-carbonized product was re-carbonized at high temperature at a heating rate of 5°C / min to a carbonization temperature of 1400°C for 2 hours. The product was then cooled naturally to room temperature, removed, crushed, and sieved to a mesh size of 400. The product was washed with 0.1 mol / L hydrochloric acid, and then with deionized water to remove residual hydrochloric acid from the hard carbon to obtain hard carbon.
[0030] Example 2
[0031] This embodiment provides a method for preparing a hard carbon material with a closed-pore structure optimized by a boron-based template, and the specific steps are as follows:
[0032] Boric acid and an appropriate amount of deionized water were added to a reaction vessel to dissolve the boric acid. Cellulose powder was then added to a ratio of 10 wt.% boric acid to cellulose powder. The mixture was mechanically stirred until thoroughly mixed. The resulting mixture was transferred to a heater for drying at 80°C for 12 hours. The dried mixture was pre-carbonized at low temperature under a nitrogen atmosphere at a heating rate of 5°C / min to a carbonization temperature of 400°C for 2 hours. After natural cooling, the boron oxide template was removed by washing with 0.1 mol / L hydrochloric acid, and residual hydrochloric acid was removed by washing with deionized water. After drying, the pre-carbonized product was re-carbonized at high temperature at a heating rate of 5°C / min to a carbonization temperature of 1400°C for 2 hours. The product was then cooled to room temperature, removed, pulverized, and sieved to a mesh size of 400. The product was washed with 0.1 mol / L hydrochloric acid, and then with deionized water to remove residual hydrochloric acid from the hard carbon to obtain hard carbon.
[0033] Example 3
[0034] This embodiment provides a method for preparing a hard carbon material with a closed-pore structure optimized by a boron-based template, and the specific steps are as follows:
[0035] Boric acid and an appropriate amount of deionized water were added to a reaction vessel to dissolve the boric acid. Bamboo powder was then added to a ratio of 5 wt.% boric acid to bamboo powder, and mechanically stirred until thoroughly mixed. The resulting mixture was transferred to a heating block for drying at 80°C for 12 hours. The dried mixture was pre-carbonized at low temperature under a nitrogen atmosphere at a heating rate of 5°C / min to a carbonization temperature of 400°C for 2 hours. After natural cooling, the boron oxide template was removed by washing with 0.1 mol / L hydrochloric acid, and residual hydrochloric acid was removed by washing with deionized water. After drying, the pre-carbonized product was re-carbonized at high temperature at a heating rate of 5°C / min to a carbonization temperature of 1400°C for 2 hours. The product was then cooled to room temperature, removed, pulverized, and sieved to a 400 mesh size. The product was then washed with 0.1 mol / L hydrochloric acid, and then with deionized water to remove any residual hydrochloric acid from the hard carbon.
[0036] Example 4
[0037] This embodiment provides a method for preparing a hard carbon material with a closed-pore structure optimized by a boron-based template, the specific contents of which are as follows:
[0038] Metaboric acid and an appropriate amount of deionized water were added to a reaction vessel to dissolve the metaboric acid. Cellulose powder was then added to a ratio of 50 wt.% metaboric acid to cellulose powder, and mechanical stirring was performed until the two were thoroughly mixed. The resulting mixture was transferred to a heater for drying at 80°C for 12 hours. The dried mixture was pre-carbonized at low temperature under a nitrogen atmosphere at a heating rate of 5°C / min, a carbonization temperature of 400°C, and a holding time of 2 hours. After natural cooling, the boron oxide template was removed by washing with 0.1 mol / L hydrochloric acid, and residual hydrochloric acid was removed by washing with deionized water. After drying, the pre-carbonized product was re-carbonized at high temperature at a heating rate of 5°C / min, a carbonization temperature of 1400°C, and a holding time of 2 hours. It was then naturally cooled to room temperature, the material was removed, crushed, and sieved to a mesh size of 400. The hard carbon was washed with 0.1 mol / L hydrochloric acid, and then the residual hydrochloric acid in the hard carbon was washed with deionized water to obtain hard carbon.
[0039] Example 5
[0040] This embodiment provides a method for preparing a hard carbon material with a closed-pore structure optimized by a boron-based template, the specific contents of which are as follows:
[0041] Boric acid and an appropriate amount of deionized water were added to a reaction vessel to dissolve the boric acid. Cellulose powder was then added to a ratio of 5 wt.% boric acid to cellulose powder. The mixture was mechanically stirred until thoroughly mixed. The resulting mixture was transferred to a heater for drying at 80°C for 12 hours. The dried mixture was pre-carbonized at low temperature under a nitrogen atmosphere at a heating rate of 5°C / min to a carbonization temperature of 600°C for 2 hours. After natural cooling, the boron oxide template was removed by washing with 0.1 mol / L hydrochloric acid, and residual hydrochloric acid was removed by washing with deionized water. After drying, the pre-carbonized product was re-carbonized at high temperature at a heating rate of 5°C / min to a carbonization temperature of 1400°C for 2 hours. The product was then naturally cooled to room temperature, removed, pulverized, and sieved to a mesh size of 400. The product was washed with 0.1 mol / L hydrochloric acid, and then with deionized water to remove residual hydrochloric acid from the hard carbon to obtain hard carbon.
[0042] Example 6
[0043] This embodiment provides a method for preparing a hard carbon material with a closed-pore structure optimized by a boron-based template, the specific contents of which are as follows:
[0044] Boric acid and an appropriate amount of deionized water were added to a reaction vessel to dissolve the boric acid. Cellulose powder was then added to a ratio of 5 wt.% boric acid to cellulose powder. The mixture was mechanically stirred until thoroughly mixed. The resulting mixture was transferred to a heater for drying at 80°C for 12 hours. The dried mixture was pre-carbonized at low temperature under a nitrogen atmosphere at a heating rate of 5°C / min, a carbonization temperature of 400°C, and a holding time of 2 hours. After natural cooling, the boron oxide template was removed by washing with 0.1 mol / L hydrochloric acid, and residual hydrochloric acid was removed by washing with deionized water. After drying, the pre-carbonized product was re-carbonized at high temperature at a heating rate of 5°C / min, a carbonization temperature of 1600°C, and a holding time of 2 hours. The product was then naturally cooled to room temperature, removed, pulverized, and sieved to a mesh size of 400. The product was washed with 0.1 mol / L hydrochloric acid, and then the residual hydrochloric acid in the hard carbon was washed with deionized water to obtain hard carbon.
[0045] Example 7
[0046] This embodiment provides a method for preparing a hard carbon material with a closed-pore structure optimized by a boron-based template, the specific contents of which are as follows:
[0047] Boric acid and an appropriate amount of deionized water were added to a reaction vessel to dissolve the boric acid. Cellulose powder was then added to a ratio of boric acid to cellulose powder of 1 wt.%, and mechanical stirring was performed until the two were thoroughly mixed. The resulting mixture was transferred to a heater for drying at 80°C for 12 hours. The dried mixture was pre-carbonized at low temperature under a nitrogen atmosphere at a heating rate of 5°C / min, a carbonization temperature of 400°C, and a holding time of 4 hours. After natural cooling, the boron oxide template was removed by washing with 0.1 mol / L hydrochloric acid, and residual hydrochloric acid was removed by washing with deionized water. After drying, the pre-carbonized product was re-carbonized at high temperature at a heating rate of 5°C / min, a carbonization temperature of 1400°C, and a holding time of 2 hours. It was then naturally cooled to room temperature, the material was removed, crushed, and sieved to a mesh size of 400. The hard carbon was washed with 0.1 mol / L hydrochloric acid, and then the residual hydrochloric acid in the hard carbon was washed with deionized water to obtain hard carbon.
[0048] Example 8
[0049] This embodiment provides a method for preparing a hard carbon material with a closed-pore structure optimized by a boron-based template, the specific contents of which are as follows:
[0050] Boric acid and an appropriate amount of deionized water were added to a reaction vessel to dissolve the boric acid. Walnut shell powder was then added to a ratio of 5 wt.% boric acid to walnut shell powder. The mixture was mechanically stirred until thoroughly mixed. The resulting mixture was transferred to a heater for drying at 80°C for 12 hours. The dried mixture was pre-carbonized at low temperature under a nitrogen atmosphere at a heating rate of 5°C / min to a carbonization temperature of 400°C for 2 hours. After natural cooling, the boron oxide template was removed by washing with 0.1 mol / L hydrochloric acid, and residual hydrochloric acid was removed by washing with deionized water. After drying, the pre-carbonized product was re-carbonized at high temperature at a heating rate of 5°C / min to a carbonization temperature of 1400°C for 2 hours. The product was then cooled to room temperature, removed, pulverized, and sieved to a 400 mesh size. The product was then washed with 0.1 mol / L hydrochloric acid, and then with deionized water to remove residual hydrochloric acid from the hard carbon.
[0051] Example 9
[0052] This embodiment provides a method for preparing a hard carbon material with a closed-pore structure optimized by a boron-based template, the specific contents of which are as follows:
[0053] Triethyl borate and an appropriate amount of deionized water were added to a reaction vessel to dissolve the triethyl borate. Cellulose powder was then added to a ratio of triethyl borate to cellulose powder of 5 wt.%, and mechanical stirring was performed until the two were thoroughly mixed. The resulting mixture was transferred to a heater for drying at 80°C for 12 hours. The dried mixture was pre-carbonized at low temperature under a nitrogen atmosphere at a heating rate of 5°C / min to a carbonization temperature of 400°C for 2 hours. After natural cooling, the boron oxide template was removed by washing with 0.1 mol / L hydrochloric acid, and residual hydrochloric acid was removed by washing with deionized water. After drying, the pre-carbonized product was re-carbonized at high temperature at a heating rate of 5°C / min to a carbonization temperature of 1400°C for 2 hours. The product was then cooled to room temperature, removed, pulverized, and sieved to a 400 mesh size. The product was washed with 0.1 mol / L hydrochloric acid, and then with deionized water to remove residual hydrochloric acid from the hard carbon to obtain hard carbon.
[0054] Example 10
[0055] This embodiment provides a method for preparing a hard carbon material with a closed-pore structure optimized by a boron-based template, the specific contents of which are as follows:
[0056] Potassium borate and an appropriate amount of deionized water were added to a reaction vessel to dissolve the potassium borate. Cellulose powder was then added to a ratio of 5 wt.% potassium borate to cellulose powder, and mechanical stirring was performed until the two were thoroughly mixed. The resulting mixture was transferred to a heater for drying at 80°C for 12 hours. The dried mixture was pre-carbonized at low temperature under a nitrogen atmosphere at a heating rate of 5°C / min, a carbonization temperature of 400°C, and a holding time of 2 hours. After natural cooling, the boron oxide template was removed by washing with 0.1 mol / L hydrochloric acid, and residual hydrochloric acid was removed by washing with deionized water. After drying, the pre-carbonized product was re-carbonized at high temperature at a heating rate of 5°C / min, a carbonization temperature of 1400°C, and a holding time of 2 hours. It was then naturally cooled to room temperature, the material was removed, crushed, and sieved to a mesh size of 400. The hard carbon was washed with 0.1 mol / L hydrochloric acid, and then the residual hydrochloric acid in the hard carbon was washed with deionized water to obtain hard carbon.
[0057] Comparative Example 1
[0058] The cellulose powder is dried in a heater for 12 hours at a temperature of 80°C. After drying, it is pre-carbonized at low temperature in a nitrogen atmosphere with a heating rate of 5°C / min, a carbonization temperature of 400°C, and a holding time of 2 hours. After natural cooling, the boron oxide template is removed by washing with 0.1mol / L, and the residual hydrochloric acid is washed with deionized water. After drying, the pre-carbonized product is re-carbonized at high temperature with a heating rate of 5°C / min, a carbonization temperature of 1400°C, and a holding time of 2 hours. It is then naturally cooled to room temperature, the material is taken out, crushed and sieved, and the mesh size is 400 mesh. It is washed with 0.1mol / L hydrochloric acid, and then the residual hydrochloric acid in the hard carbon is washed with deionized water to obtain hard carbon.
[0059] Comparative Example 2
[0060] The bamboo powder is dried in a heater for 12 hours at a temperature of 80°C. After drying, it is pre-carbonized at low temperature in a nitrogen atmosphere with a heating rate of 5°C / min, a carbonization temperature of 400°C, and a holding time of 2 hours. After natural cooling, the boron oxide template is removed by washing with 0.1mol / L, and the residual hydrochloric acid is washed with deionized water. After drying, the pre-carbonized product is re-carbonized at high temperature with a heating rate of 5°C / min, a carbonization temperature of 1400°C, and a holding time of 2 hours. It is then naturally cooled to room temperature, the material is taken out, crushed and sieved, and the mesh size is 400 mesh. It is washed with 0.1mol / L hydrochloric acid, and then the residual hydrochloric acid in the hard carbon is washed with deionized water to obtain hard carbon.
[0061] Comparative Example 3
[0062] The walnut shell powder is dried in a heater for 12 hours at a temperature of 80°C. After drying, it is pre-carbonized at low temperature in a nitrogen atmosphere with a heating rate of 5°C / min, a carbonization temperature of 400°C, and a holding time of 2 hours. After natural cooling, the boron oxide template is removed by washing with 0.1mol / L, and the residual hydrochloric acid is washed with deionized water. After drying, the pre-carbonized product is re-carbonized at high temperature with a heating rate of 5°C / min, a carbonization temperature of 1400°C, and a holding time of 2 hours. It is then naturally cooled to room temperature, the material is taken out, crushed and sieved, and the mesh size is 400 mesh. It is washed with 0.1mol / L hydrochloric acid, and then the residual hydrochloric acid in the hard carbon is washed with deionized water to obtain hard carbon.
[0063] Comparative Example 4
[0064] Potassium chloride and an appropriate amount of deionized water were added to the reaction vessel to dissolve the potassium chloride. Cellulose powder was then added to a ratio of potassium chloride to cellulose powder of 5 wt.%, and mechanically stirred until the two were completely mixed. The resulting mixture was transferred to a heater for drying at 80°C for 12 hours. The dried mixture was pre-carbonized at low temperature under a nitrogen atmosphere at a heating rate of 5°C / min, a carbonization temperature of 400°C, and a holding time of 2 hours. After natural cooling, the boron oxide template was removed by washing with 0.1 mol / L HCl, and residual hydrochloric acid was washed with deionized water. After drying, the pre-carbonized product was re-carbonized at high temperature at a heating rate of 5°C / min, a carbonization temperature of 1400°C, and a holding time of 2 hours. It was then naturally cooled to room temperature, the material was removed, crushed, and sieved to a mesh size of 400. The hard carbon was washed with 0.1 mol / L hydrochloric acid, and the residual hydrochloric acid in the hard carbon was washed with deionized water to obtain hard carbon.
[0065] Comparative Example 5
[0066] Boric acid and an appropriate amount of deionized water were added to a reaction vessel to dissolve the boric acid. Cellulose powder was then added to a ratio of 70 wt.% boric acid to cellulose powder. The mixture was mechanically stirred until thoroughly mixed. The resulting mixture was transferred to a heater for drying at 80°C for 12 hours. The dried mixture was pre-carbonized at low temperature under a nitrogen atmosphere at a heating rate of 5°C / min to a carbonization temperature of 400°C for 2 hours. After natural cooling, the boron oxide template was removed by washing with 0.1 mol / L hydrochloric acid, and residual hydrochloric acid was removed by washing with deionized water. After drying, the pre-carbonized product was re-carbonized at high temperature at a heating rate of 5°C / min to a carbonization temperature of 1400°C for 2 hours. The product was then cooled to room temperature, removed, pulverized, and sieved to a 400 mesh size. The product was washed with 0.1 mol / L hydrochloric acid, and then with deionized water to remove residual hydrochloric acid from the hard carbon to obtain hard carbon.
[0067] Test Example 1
[0068] The electrochemical performance of the finished product was tested using the half-cell test method:
[0069] The hard carbon negative electrode active material samples (Examples 1-10, Comparative Examples 1-5), a conductive agent (SP) and a binder (CMC) were mixed uniformly with a certain amount of deionized water in a mass ratio of 85:12:3 and then coated on a current collector to prepare the sodium ion battery negative electrode plate. The plate was pressed into a circular plate with a diameter of 12 mm and dried at 105°C for 12 hours for use. In a glove box, a metal sodium sheet was used as the counter electrode, the electrolyte was 1M NaPF6 in DME = 100 Vol%, and Whatman GF / D ultrafine glass fiber was used as the separator to assemble a button cell. The battery was tested using a LANHE CT3002A battery tester under the conditions of a current density of 20 mA / g and a voltage range of 0.005-3 V. The cellulose-based hard carbon negative electrode material prepared in Example 1 showed a first-cycle capacity of 363 mAh / g at 20 mA / g and a first coulombic efficiency of 94%.
[0070] The electrochemical performance of the batteries assembled from Examples 1-10 and Comparative Examples 1-5 was tested at a current density of 20 mA / g and a voltage range of 0.005-3 V. The test results are shown in Table 1.
[0071] Table 1
[0072]
[0073]
[0074] According to the results in Table 1, the use of boron-based templates can effectively control the closed-pore structure of biomass-based hard carbon materials. Among them, the closed-pore volume of Example 8 reaches 0.0637 cm 3 / g has the highest value, which is significantly improved compared with Comparative Example 4. The optimization of this closed-pore structure is directly reflected in the electrochemical performance: Example 8 not only shows the highest first-cycle capacity (373mAh / g), but its first coulombic efficiency also reaches 95%, which is significantly improved compared with other comparative examples. This result fully confirms the key role of boron-based templates in the optimization of the closed-pore structure of hard carbon materials. However, when the addition amount of boron-based templates is increased to 70% (Comparative Example 5), due to the agglomeration effect of the template, its structural regulation effect is significantly weakened, and the closed-pore volume is reduced to 0.0522cm 3 / g (a decrease of 18.1% compared with Example 8), resulting in a decrease in sodium storage capacity to 334 mAh / g and a slight decrease in the first coulombic efficiency to 92%. This phenomenon confirms that there is an optimal range for the amount of boron-based template, and excessive addition will inhibit its positive effect.
[0075] The charge and discharge curves of Example 1 and Comparative Example 1 are shown in FIG. Figure 1 As shown. Figure 1The results show that the material's charge-discharge curve exhibits typical hard carbon characteristics, with a slope above 0.1V and a plateau below 0.1V. This plateau is associated with the incorporation of sodium ions into the closed-pore structure of the hard carbon. The boron-based template significantly increases the closed-pore structure, leading to a significant increase in the plateau.
[0076] The hard carbon materials prepared in Example 1 and Comparative Example 1 were used as samples and XRD tests were performed respectively. The results are as follows: Figure 2 As shown. Figure 2 The results show that the hard carbon materials prepared in Example 1 and Comparative Example 1 both have a typical graphite structure, showing the 002 crystal plane and 100 crystal plane of graphite at 23.0° and 43.4°.
[0077] The hard carbon materials prepared in Examples 1-10 and Comparative Examples 1-4 were used as research objects to analyze the correlation between closed pore volume and sodium storage capacity. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the closed-pore volume and sodium storage capacity show an obvious positive correlation trend, indicating that the optimization of the closed-pore structure of hard carbon materials by boron-based templates can effectively improve their sodium storage performance.
[0078] The hard carbon material prepared in Example 8 was used as a sample and TEM images were taken. The results are as follows: Figure 4 As shown. Figure 4 The results show that all hard carbon samples present a locally ordered structure, which is due to the important role of the boron-based template as a closed-pore structure regulator.
[0079] The above embodiments are preferred implementations of the present invention, but the implementations of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be considered as equivalent replacement methods and are included in the scope of protection of the present invention.
Claims
1. A method for preparing a biomass-based hard carbon material with a closed-cell structure optimized by a boron-based template, characterized in that: The following steps are involved: (1) solid-liquid mixing of biomass and a boron-based template aqueous solution, and drying; (2) The mixed material is subjected to two carbonization treatments, firstly, low-temperature pre-carbonization is performed to convert the boron-based template into a boron-based template at low temperature and embed it into the biomass precursor carbon. After natural cooling, the boron-based template is washed to remove the boron-based template. Then, the mixed material is subjected to high-temperature re-carbonization, followed by crushing, acid washing, water washing and drying in sequence to obtain the hard carbon material.
2. The preparation method according to claim 1, characterized in that In step (1), the biomass is at least one of bamboo, pulp, lignin, walnut shells, tea oil shells, xylose residue, coconut shells, fruit cores, peanut shells, nut skins, corn cobs, straw and cellulose powder; and the boron template is at least one of boric acid, borax, triethyl borate, trimethyl borate, metaboric acid, sodium metaborate and potassium borate.
3. The preparation method according to claim 1, characterized in that The mass ratio of the boron-based template agent to the biomass is 0.01:1-0.5:
1.
4. The preparation method according to claim 1, characterized in that In step (2), the low-temperature pre-carbonization is carried out under the protection of an inert atmosphere, and the carbonization conditions include: a heating rate of 2-20°C / min, a temperature of 200-600°C, and a holding time of 10-300min.
5. The preparation method according to claim 1, characterized in that In step (2), the high-temperature recarbonization is carried out under the protection of an inert atmosphere, and the carbonization conditions include: a heating rate of 2-20°C / min, a temperature of 1200-1600°C, and a holding time of 10-300min.
6. The preparation method according to claim 4 or 5, characterized in that The inert atmosphere is nitrogen or argon.
7. The preparation method according to claim 1, characterized in that In step (2), the boron-based template is removed by washing with dilute hydrochloric acid at a concentration of 0.1-3 mol / L; and deionized water is used to wash the residual hydrochloric acid in the hard carbon.
8. The preparation method according to claim 1, characterized in that In step (2), the pickling adopts an acidic solution including at least one of hydrochloric acid, sulfuric acid, phosphoric acid and nitric acid, and the acid concentration is 0.1-3 mol / L.
9. A biomass-based hard carbon material with a closed-pore structure optimized by a boron-based template obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the biomass-based hard carbon material with a closed-pore structure optimized by a boron-based template as claimed in claim 9 as a negative electrode material for sodium ion batteries.